2015
DOI: 10.1016/j.pupt.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress as activators of sensory nerves for cough

Abstract: Excessive activation of the cough reflex is a major clinical problem in respiratory diseases. The cough reflex is triggered by activation of nociceptive sensory nerve terminals innervating the airways by noxious stimuli. Oxidative stress is a noxious stimuli associated with inhalation of pollutants and inflammatory airway disease. Here, we discuss recent findings that oxidative stress, in particular downstream of mitochondrial dysfunction, evokes increased electrical activity in airway nociceptive sensory nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“… 43 TRPA1 can be activated by electrophiles through covalent modification of cysteine residues on the cytoplasmic N-terminus of the channel, 44 , 45 and this explains its sensitivity to reactive species that have an innate oxidative potential or the ability to generate intracellular oxidative stress. 44 , 46 In the present study we confirm that H 2 O 2 was also able to depolarize the vagus nerve in a TRPA1-dependent manner 30 , 47 and that responses to H 2 O 2 and DEP-OE were inhibited by the general antioxidant NAC. This is in general agreement with previous studies in which the effects of DEPs have been inhibited by application of NAC.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“… 43 TRPA1 can be activated by electrophiles through covalent modification of cysteine residues on the cytoplasmic N-terminus of the channel, 44 , 45 and this explains its sensitivity to reactive species that have an innate oxidative potential or the ability to generate intracellular oxidative stress. 44 , 46 In the present study we confirm that H 2 O 2 was also able to depolarize the vagus nerve in a TRPA1-dependent manner 30 , 47 and that responses to H 2 O 2 and DEP-OE were inhibited by the general antioxidant NAC. This is in general agreement with previous studies in which the effects of DEPs have been inhibited by application of NAC.…”
Section: Discussionsupporting
confidence: 84%
“… 29 Oxidative stress and the production of electrophiles have been shown to activate TRPA1 through covalent modification of cysteine residues. 30 , 31 , 32 The oxidant H 2 O 2 depolarized isolated guinea pig vagus nerve in a concentration-dependent manner (see Fig E5 , A , in this article's Online Repository at www.jacionline.org ). Janssen 130 (10 μmol/L) but not vehicle (0.1% DMSO) or TRPV1 antagonism significantly inhibited H 2 O 2 -induced depolarization in the guinea pig vagus nerve (see Fig E5 , B ).…”
Section: Resultsmentioning
confidence: 99%
“…The inflammation includes neurogenic and contribution of various cells, such as eosinophils, lymphocytes, neutrophils, and mast cells 18 20 . Furthermore, Clark et al 12 recently revealed that mitochondrial reactive oxygen species activate airway sensory nerves, via TRP channels, and protein kinase C, and finally evoke cough reflexes. Citrate 21 , 22 exhibits anti-inflammatory and antioxidative properties as discussed below; thus, suggesting that decreased citric acid may fail to protect from airway inflammation and oxidative stress is plausible, which in turn leads to prolonged cough (Figure S2a).…”
Section: Discussionmentioning
confidence: 99%
“…Other potential mechanisms that underlie cough hypersensitivity syndrome include ion channels on C-fibers or airway sensory nerves, such as transient receptor potential (TRP) V1, V4, and A1 7 and prostaglandin E2 8 . Furthermore, the airway sensory nerves can be activated with airway inflammation 9 11 and oxidative stress 12 . However, the mechanisms that underlie prolonged or chronic cough remain largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that increased airway oxidative stress is associated with chronic cough [ 24 ]. Recent work has indicated that oxidative stress, in particular downstream of mitochondrial dysfunction, activates airway nociceptive sensory nerves that may contribute to an excessive cough reflex [ 25 ]. One of the mechanisms underlying oxidative stress is through the increased expression of transforming growth factor β (TGFβ) levels in BALF and in the bronchial mucosa and in particular ASMCs and the airway epithelium of patients with chronic cough [ 26 ].…”
Section: Discussionmentioning
confidence: 99%